The Scoping Review of Systematic Instruction Literature for Individuals With Disabilities: Trends in Türkiye From 1983 to 2022 - Yücesoy-Özkan, Şerife; MART, SİMA; Sayar, Kübra; Altun, Dilara Ecem; Gülboy, Emrah; Kaya, Feyat; Öncül, Nuray (Routledge Journals, Taylor & Francis Ltd., 2024)
This study used a scoping review to examine the systematic instruction studies for individuals with disabilities published in the last four decades (1983-2022) in Turkiye. We included 332 single-case and 61 group experimental studies. We collected inter-rater reliability data for 30% of the studies and determined that the mean of inter-rater coefficients was 99.2%. The findings indicate that the studies have been mainly self-funded and performed by one or two special education researchers. Studies conducted with single-case studies were more prevalent than group experimental studies. Male participants were more than females, and more school-age children than infants and adults. Participants with intellectual disabilities and autism were the most frequently involved, and school-related academic and cognitive skills were the most commonly targeted. The most frequently used interventions were response prompting strategies, strategy instruction, video modelling and prompting, and direct instruction. Finally, we discussed the findings and made recommendations for practice and future research.
Keywords: Scoping Review; Systematic Instruction; Individuals With Disabilities; Single-Case Experimental Studies; Group Experimental Studies